2022
DOI: 10.3389/fimmu.2022.1068091
|View full text |Cite
|
Sign up to set email alerts
|

3D tumor explant as a novel platform to investigate therapeutic pathways and predictive biomarkers in cancer patients

Abstract: Immunotherapy with immune checkpoint inhibitors can induce durable clinical responses in different human malignancies but the number of responding patients remains globally modest. The limited therapeutic efficacy of ICI depends on multiple factors, among which the immune suppressive features of the tumor microenvironment play a key role. For this reason, experimental models that enable dissection of the immune-hostile tumor milieu components are required to unravel how to overcome resistance and obtain full-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…TME organoid models based on microfluidic technology can preserve immune cells and stromal cells, but the next challenge is to improve the success rate and ensure the stability of cultures ( Yuki et al, 2020 ). The in vitro 3D culture technology PDE, while preserving the complete composition and structure of patient tissue, is limited in its development due to difficulty in conducting high-throughput drug screening and relatively short window for operation ( Powley et al, 2020 ; Rodolfo et al, 2022 ). Formation of the tumor microvasculature and distribution of oxygen and nutrients from MM to other organs are also crucial for reproducing the TME in the body ( Rodolfo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TME organoid models based on microfluidic technology can preserve immune cells and stromal cells, but the next challenge is to improve the success rate and ensure the stability of cultures ( Yuki et al, 2020 ). The in vitro 3D culture technology PDE, while preserving the complete composition and structure of patient tissue, is limited in its development due to difficulty in conducting high-throughput drug screening and relatively short window for operation ( Powley et al, 2020 ; Rodolfo et al, 2022 ). Formation of the tumor microvasculature and distribution of oxygen and nutrients from MM to other organs are also crucial for reproducing the TME in the body ( Rodolfo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro 3D culture technology PDE, while preserving the complete composition and structure of patient tissue, is limited in its development due to difficulty in conducting high-throughput drug screening and relatively short window for operation ( Powley et al, 2020 ; Rodolfo et al, 2022 ). Formation of the tumor microvasculature and distribution of oxygen and nutrients from MM to other organs are also crucial for reproducing the TME in the body ( Rodolfo et al, 2022 ). The development of non-invasive methods (e.g., liquid biopsy) will further advance organoids as a platform for the prediction and drug screening of personalized treatment for patients ( Maru et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Karekla et al Further developed another type of PDE in which tissues were cultured on a membrane with a pore size of 0.4 µm at the air-liquid interface and demonstrated that the PDE response to cisplatin was significantly correlated with patient survival [ 24 ]. Rodolfo et al have also developed original PDEs using a Rotary Cell Culture System (RCCS) in a bioreactor [ 72 ].…”
Section: Patient-derived Ex Vivo Culturesmentioning
confidence: 99%
“…Rodolfo et al used a bioreactor to establish PDEs with prolonged survival and demonstrated their immunologic response to PD-1 treatment by immunostaining, suggesting the potential of PDEs for prediction of ICI response [ 72 ]. Ding et al have also developed an immunostaining-based endpoint assay to detect the T-cell immune response against tumor cells by using MOSs containing both patient-derived tumor organoids and their associated immune cells [ 28 ].…”
Section: Endpoint Assays For Functional Testingmentioning
confidence: 99%